The Effectiveness of an Integrated Training Package Based on Time Perspective Therapy and Positive Therapy on Psychological Coherence and Happiness in Depressed Patients - Hemmati, Mohammad; Tizdast, Taher; Jadidi, Mohsen (Mental Health and Lifestyle Journal, 2025)
The present study was conducted with the aim of determining the effectiveness of an integrated training package based on time perspective therapy and positive therapy on psychological coherence and happiness in depressed patients. This was a quasi-experimental study, and the statistical population consisted of 40 patients with moderate depression who had active medical records in counseling centers with a diagnosis of depression in Tehran during 2022 (from July 2022 to August 2022). Using convenience sampling, they were randomly assigned to experimental and control groups. Initially, all participants completed a pre-test. Then, the experimental group received the integrated training package intervention (in 11 group sessions, each lasting 2 hours). Subsequently, a post-test was administered to both groups. Data collection instruments included the Beck Depression Inventory–Short Form (1992), the Flensborg-Madsen Sense of Coherence Questionnaire (2006), and the Argyle and Lu Happiness Questionnaire (1989). Data were analyzed using SPSS software. The findings indicated that the integrated training package based on time perspective therapy and positive therapy had a significant effect on the psychological coherence and happiness of depressed patients (P < 0.05). Based on the results, this integrated training package can be applied to improve the treatment of psychological disorders in depressed patients.